Interaction Effect of Sex and Body Mass Index on Gray Matter Volume - Huang, Yufei; Li, Xianjie; Jackson, Todd; Chen, Shuaiyu; Meng, Jie; Qiu, Jiang; Chen, Hong (Frontiers in Human Neuroscience, 2019)
Objective Few studies have investigated sex differences in brain structure associated with obesity, and the related findings are inconsistent. In this study, we aimed to investigate the effect of sex × body mass index (BMI) interactions on gray matter volume (GMV), and to determine the implications of any structural differences. Methods The final sample comprised 653 participants (449 women) who were assessed using voxel-based morphology analysis of T1-weighted magnetic resonance images. The main effects of BMI and sex as well as the BMI × sex interaction on GMV were assessed. A subset of 410 participants (291 women) underwent whole brain resting-state functional connectivity (rsFC) analysis to investigate sex differences in the seed (interaction) region. Results A significant BMI × sex interaction was observed in the left anterior cingulate cortex (ACC), while GMV was negatively correlated with BMI in men but not in women. The rsFC between the left ACC and the caudate was lower in men than in women. Within the entire sample, the insula, caudate, and medial frontal cortex activities were negatively correlated with BMI while the cerebellum and postcentral gyrus activities were positively correlated with BMI. Conclusions Our findings address the interaction effect of BMI and sex on GM alterations. Men were more vulnerable to BMI-related GMV reductions, which reflect functional alterations.